Adapting Very Brief Advice (VBA) on smoking for use in low-resource settings: experience from the FRESH AIR project. (September 2019) - McEwen, Andy; Pooler, Jill; Lionis, Christos; Papadakis, Sophia; Tsiligianni, Ioanna; Anastasaki, Marilena; An, Pham Le; Vinh, Nguyen Nhu; Binh, Pham Duong Uyen; Quỳnh, Nguyĕn Nhật; Tuãn, Trãn Diêp; Talant, Sooronbaev; et al.
Abstract: Introduction: Very Brief Advice (VBA) on smoking is an evidence-based intervention and a recommended clinical practice for all healthcare professionals in the UK. Aims: We report on experience from the FRESH AIR project in adapting the VBA model and training in three low-resource settings: Greece, Vietnam and Kyrgyzstan. Methods: Using a participatory research process, UK experts and local stakeholders conducted an environmental scan and needs assessment to examine the VBA intervention model, training materials and recommend adaptations to the local context. Two VBA training sessions were piloted in each country to inform adaptation. A final training tool kit was developed in the local language. Results: In each country, the VBA on smoking intervention model remained primarily intact. The lack of a formal smoking cessation system to refer motivated clients in two countries required adaptation of the ACT component of the model. A range of local adaptations to the training resources were made in all three countries to ensure cultural appropriateness as well as enhance key messages including expanding training on nicotine addiction, second-hand smoke and pharmacotherapy. Conclusions: Implementation of VBA requires sensitive, collaborative, local and cultural adaptation if it is to be achieved successfully. Trial registration: Trial ID# NTR5759 Critical appraisal tools: The Standards for Reporting Implementation Studies (StaRI) statement: https://www.equator-network.org/reporting-guidelines/stari-statement/